Mobile DJ handbook : how to start and run a profitable mobile disc jockey service - Zemon, Stacy, 1960- (Focal Press, 2003)
The Mobile DJ Handbook, Second Edition continues to be an excellent guide for novice and experienced DJs looking to build a successful career as the owner-operator of a mobile disc jockey service. Complete with practical tips, expert advice, and creative strategies, this book serves as the perfect guide on how to market and sell your services as well as develop and expand your business. This book contains information on becoming a professional, securing bookings, buying equipment and music, and running party dances, contests, and ga.